Studies on Metabolism of Urokinase and Mechanism of Thrombolysis by Urokinase - Ueno, Tatsuo; Kobayashi, Norio; Maekawa, Tadashi (Thrombosis and Haemostasis, 1979)
Pharmacokinetics of intravenously injected 125I-labeled urokinase (125I-UK) of a molecular weight of 33,000 daltons in normal rabbits and patients with various diseases were investigated. The plasma clearance of 125I-UK in rabbits was described by a biexponential curve within six hours with a half-life of 8 minutes, 2.3 hours, respectively. The radioactivity in the liver and kidneys 15 minutes after iv injection with 125I-UK was 9.6% and 14.0% of the radioactivity injected, respectively. Approximately 80% of the total radioactive material injected was excreted in the urine in 18 hours. No increase in activator activity in the urine was observed after a large amount of UK injection. Activity uptake of 125I-UK by experimentally induced arterial thrombus was little. Lysis of the stasis thrombus was produced by injecting 7.5 × 104 IU of UK in only one out of 8 rabbits. In vitro contact experiment revealed that transfer of 125I-UK to plasma clot is slow (24 hours for 10% of 125I-UK by plasma clot). In 4 patients plasma clearance of 125I-UK was essentially similar to that in rabbits. From the results obtained optimal dosage regimen of UK administration for complete thrombolysis in vivo was discussed.